Modelagem em reguladores de tensão monofásicos com 32 degraus para estudos em regime permanente e transitório - Felício, Jordana Rodrigues (2006)
In recent years, the growth of the electrical system associated with non ideal conditions can compromise the normal operation devices. This fact is becoming extremely important, as much the consumers as for the electric utilities. In this way, the electrical agencies are more concerned about, for example, the distribution voltage levels. With this in mind, the voltage regulation device has been one of the more used equipment with the purpose of voltage levels correction or adequacy, either agricultural or urban site. This equipment, in its usual structure, is composed by an autotransformer with a tap automatic mechanism that presents a high time delay and does not apply to the shortduration voltage variations requirements, imposed by electrical standards. Aiming at adjusting the voltage regulator to the distribution requirements, that is, to minimize its time delay to any voltage variation, transitory studies of tap commutation must be elaborated. This work aims at modelling a single-phase 32 step voltage regulator in a computational simulator called ATP (EMTP). This modelling is based on the core magnetic characteristics and it is constituted of linear and non linear inductances representing the flux through the air and through the steel core. By considering the laboratory difficulties to make measurements in a voltage medium equipment (13.8 kV), a typical voltage regulator prototype was constructed (220 V) and a laboratory arrangement was used to validate the corresponding modelling.